The Effect of Massage Therapy on Pain Intensity in Fracture Patients : A Systematic Review - Gunawan, Gunawan; Upoyo, Arif Setyo (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Pain disorders are common in patients with fracture disease. Massage therapy is considered effective for reducing the pain intensity of fracture patients. The Purpose of the Systematic review is to investigate the effect of massage therapy on pain intensity in patients with fractures. Methods: The English full-text research publications from 2012 to 2023 that were found using the Google Scholar, Pubmed, and Science Direct databases were published in China (4 articles) and Iran (2 articles). Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) techniques, articles were chosen. Quality assessment was conducted using the Joanna Briggs Institute (JBI) Critical Appraisal Skills Programme. Six articles examined pain intensity with the usual Visual Analogue Scale (VAS). Results: The outcomes achieved were Six articles. It has also been demonstrated to lessen fracture patients' pain. Numerous massage therapy techniques, such as foot massage, reflexology massage, auricular acupressure, and elbow massage therapy, were employed in the studies that made up the evaluation. In the intervention and control groups, the mean pain intensity scores before and after the intervention were 5.72 + 0.97 and 5.66 + 0.92, respectively. The three measures of pain intensity in the intervention group showed a significant difference, according to the Friedman test. Conclusion: The analysis concludes that massage therapy is a highly effective means of reducing pain in those who have suffered fractures. More investigation is need to confirm these results and assess different forms of massage therapy, though.